Optimization design of the octagonal water diffuser with uniform flow orifice plate. (15th December 2021) - Tang, Jiali; Shi, Yuyang; OuYang, Zhengrong
Highlights: In this paper, based on the computational fluid dynamics software FLUENT and other analysis tools, the water diffuser scheme of naturally stratified water storage system was optimized. Based on the scheme of octagonal diffuser and uniform flow orifice plate, the simulation analysis of the outlet mode of water distribution pipe and the opening parameters of orifice plate were carried out. According to the numerical simulations on the different volume water storage tanks, the comprehensive analysis showed that the diffusion performance of circular opening was better than slot opening, and the thickness of thermocline was thinner when the opening ratio of the orifice plate was 20% than the case of 30% and 45%. In addition, it was pointed out that the porous media model could almost replace the two-dimensional actual opening model under the low opening rate. The optimization results will provide a reference for the scientific application of octagonal water diffuser with uniform flow orifice plate in naturally stratified water storage system. ①Based on the computational fluid dynamics software FLUENT and other analysis tools, the water diffuser scheme of naturally stratified water storage system was optimized. ②Based on the scheme of octagonal diffuser and uniform flow orifice plate, the simulation analysis of the outlet mode of water distribution pipe and the opening parameters of orifice plate were carried out. ③The effect of the vertical outlet of the circular hole was equivalent to that of the symmetrical inclined outlet of both sides, and the outlet of the circular hole was better than that of the slot. ④The thickness of thermocline was thinner when the opening ratio of the orifice plate was 20% than the case of 30% and 45%. ⑤It was pointed out that the porous media model could almost replace the two-dimensional actual opening model under the low opening rate.The optimization results will provide a reference for the scientific application of octagonal water diffuser with uniform flow orifice plate in naturally stratified water storage system. Abstract: Energy storage technology has been widely used in many fields, mainly due to the continuous development of social economy, resulting in increasing power consumption and peak valley load difference. This technology can play the role of adjusting the electric network load. Among them, water storage technology is the most representative. Naturally stratified technology is the most economical and effective method in chilled water storage technique and its core is the design of water diffuser. Octagonal water diffuser with the uniform flow orifice plate is a more effective water distribution mode in the naturally stratified chilled water storage system. In order to get the higher chilled water storage efficiency, the fluid dynamics software was used to make an optimization research on its parameters. Based on the scheme of octagonal diffuser and uniform flow orifice plate, the simulation analysis of the outlet mode of water distribution pipe and the opening parameters of orifice plate were carried out. According to the numerical simulations on the different volume water storage tanks, the comprehensive analysis showed that the diffusion performance of circular opening was better than slot opening, and the thickness of thermocline was thinner when the opening ratio of the orifice plate was 20% than the case of 30% and 45%. In addition, it was pointed out that the porous media model could almost replace the two-dimensional actual opening model under the low opening rate.